Direct Synthesis and Delamination of Swollen Layered Ferrierite for the Reductive Etherification of Furfural. Issue 16 (15th June 2022) - Wang, Jilong; Fan, Yaqi; Guo, Xiaowen; Gu, Qingyi; Jiang, Jingang; Guan, Yejun; He, Xiao; Ma, Yanhang; Xu, Hao; Wu, Peng
Abstract: A swollen ferrierite structure (denoted as ECNU‐35P) was directly synthesized with a commercially available surfactant of decamethonium hydroxide as bifunctional organic structure‐directing agent (OSDA). ECNU‐35P, with elastic long‐chain surfactant intercalating the neighboring FER layers, had a much wider interlayer spacing than previously reported FER‐type layered precursors of PLS‐3 and PREFER. The phase delamination of ECNU‐35P was readily realized without additional swelling process that is destructive to zeolite frameworks. The non‐corrosive delaminated derivative (DECNU‐35) was composed of the FER nanosheets with 4 nm‐thickness. With large external surface area, abundant mesopores and moderate acidity, Pd/DECNU‐35 served as highly active and robust catalysts in the reductive etherification of biomass furfural, providing a high yield of 74 % for the biofuel of furfuryl ethyl ether. Abstract : A new FER layered zeolite (ECNU‐35P) with interlayer swollen structure has been hydrothermally synthesized using decamethonium hydroxide as OSDA. Its phase delamination (DECNU‐35) can be mildly realized, endowing the resultant porous materials with large external specific surface area and attractive catalytic performance in the selective production of biofuels.